2021
DOI: 10.1111/joa.13392
|View full text |Cite
|
Sign up to set email alerts
|

In situ localization of diacylglycerol lipase α and β producing an endocannabinoid 2‐arachidonoylglycerol and of cannabinoid receptor 1 in the primary oocytes of postnatal mice

Abstract: In order to understand the mechanism of the endocannabinoid (eCB) signal, which has so far been shown to work in oocyte genesis and maturation, it is critical to clarify detailed localization of the eCB synthesizing enzyme molecules as well as receptors for eCBs in oocytes in the ovary in situ. For this purpose, diacylglycerol lipase (DGL) α and β are involved in the synthesis of an eCB 2-arachidonoylglycerol (2-AG). DGLα/β and the cannabinoid receptor 1 (CB1) for 2-AG were shown to be localized to the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…In our recent study, 6 the expression of CB1 in the ovary of adult female mice was confirmed with a band of 51 kDa in Western blots, whose size is compatible with that reported in mouse brain with the same antibody. 7…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…In our recent study, 6 the expression of CB1 in the ovary of adult female mice was confirmed with a band of 51 kDa in Western blots, whose size is compatible with that reported in mouse brain with the same antibody. 7…”
Section: Resultssupporting
confidence: 83%
“…In total, 10 female ICR mice at a stage of postnatal 8 weeks were purchased from the National Laboratory Animal Center, Bangkok, Thailand. As the expression bands for CB1 at its authentic molecular size and no differences in expression of the molecule among the four estrous stages were already confirmed in Western blots of adult ovaries of the same resource in our previous study, 6 mice at the diesterus stage were used in this study.…”
Section: Methodssupporting
confidence: 60%
See 2 more Smart Citations
“…There are many studies for effects of the eCB system on the ovarian events such as folliculogenesis, oogenesis and oocyte maturity until fertilization and preimplantation of embryo [9] and presents the eCB system immunoreactivities by several authors to assume the results of eCB, which localized on the oocyte maturity after restart of meiosis I [8,10,11]. In my recent study, the novel knowledge showed the expression and localization of CB1, DAGL-α and DAGL-β that it was first reported in oocytes of mouse ovary [12]. Additionally, the eCB signaling molecules including CB1, CB2 and enzymes for degradation as well as FAAH and MGLL were studied to locate in the follicle, corpus luteum and corpus albicans of human ovary [2,8].…”
Section: Introductionmentioning
confidence: 96%